Platelet-Rich Fibrin–Augmented Gap-Bridging Strategy in Rabbit Anterior Cruciate Ligament Repair. Issue 3 (March 2023) - Weng, Pei-Wei; Chen, Chih-Hwa; Lin, Yi-Cheng; Chen, Kuan-Hao; Yeh, Yi-Yen; Lai, Jen-Ming; Chiang, Chang-Jung; Wong, Chin-Chean
Background: We assessed the efficacy of a novel platelet-rich fibrin (PRF)–augmented repair strategy for promoting biological healing of an anterior cruciate ligament (ACL) midsubstance tear in a rabbit model. The biological gap-bridging effect of a PRF scaffold alone or in combination with rabbit ligamentocytes on primary ACL healing was evaluated both in vitro and in vivo. Hypothesis: A PRF matrix can be implanted as a provisional fibrin-platelet bridging scaffold at an ACL defect to facilitate functional healing. Study Design: Controlled laboratory study. Methods: The biological effects of PRF on primary rabbit ligamentocyte proliferation, tenogenic differentiation, migration, and tendon-specific matrix production were investigated for treatment of cells with PRF-conditioned medium (PRFM). Three-dimensional (3D) lyophilized PRF (LPRF)–cell composite was fabricated by culturing ligamentocytes on an LPRF patch for 14 days. Cell-scaffold interactions were investigated under a scanning electron microscope and through histological analysis. An ACL midsubstance tear model was established in 3 rabbit groups: a ruptured ACL was treated with isolated suture repair in group A, whereas the primary repair was augmented with LPRF and LPRF-cell composite to bridge the gap between ruptured ends of ligaments in groups B and C, respectively. Outcomes—gross appearance, magnetic resonance imaging, and histological analysis—were evaluated in postoperative weeks 8 and 12. Results: PRFM promoted cultured ligamentocyte proliferation, migration, and expression of tenogenic genes (type I and III collagen and tenascin). PRF was noted to upregulate cell tenogenic differentiation in terms of matrix production. In the 3D culture, viable cells formed layers at high density on the LPRF scaffold surface, with notable cell ingrowth and abundant collagenous matrix depositions. Moreover, ACL repair tissue and less articular cartilage damage were observed in knee joints in groups B and C, implying the existence of a chondroprotective phenomenon associated with PRF-augmented treatment. Conclusion: Our PRF-augmented strategy can facilitate the formation of stable repair tissue and thus provide gap-bridging in ACL repair. Clinical Relevance: From the translational viewpoint, effective primary repair of the ACL may enable considerable advancement in therapeutic strategy for ACL injuries, particularly allowing for proprioception retention and thus improved physiological joint kinematics.